Learning to Program with Visual Basic and .NET Gadgeteer - Sentance, Sue; Johnston, Steven; Hodges, Steve; Kučera, Jan; Scott, James; Schwiderski-Grosche, Scarlet (Microsoft Research, 2013)
This book is intended for school students and others learning to program in Visual Basic. It assumes no prior knowledge of programming, electronics, Visual Basic or the Visual Studio environment. Programming concepts are introduced and explained throughout the book. Each chapter is structured in a similar way: firstly a new concept to be learned is introduced, secondly there is a step-by-step tutorial on how to develop a simple example in Gadgeteer which uses that concept, and finally a set of exercises is given which enable the reader to practice the main points. This last step is the most important: when learning to program, practicing new programing skills is crucial! Answers to all the exercises are available at http://gadgeteering.net.